PROSELYTIZING EXPANSION OF TABLIGHI JAMAAT IN WETU TELU INDIGENOUS COMMUNITY IN BAYAN, NORTH LOMBOK - Hamdi, Saipul; Nasrullah, Arif; Awalia, Hafizah; Malik, Firdaus Abdul ; Haromain, Nurul (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2023)
Tablighi Jamaat's (TJ) proselytizing activity has had a significant impact on improving the religious practices of the community not only in India, where TJ was born and evolved, but also in other nations where they preach, including Indonesia. TJ's da'wah has reached rural places with strong customs. The purpose of this study is to investigate the growth and influence of TJ's da'wah movement in the Wetu Telu Bayan indigenous community in North Lombok. This study employs qualitative data collection approaches such as participant observation, in-depth interviews, and focus group discussions. According to the findings of this study, the beginning of TJ's da'wah expansion began with the movement of young people from the hamlet who were still in high school to Jamaah Tabligh's da'wah. He was successful in enticing the community to join by presenting various programs such as Safari Friday (Safari Jumat), a three-day church for spiritual growth. This program was strengthened by the Lombok Uatara Regent's program, namely emotional treatment (Termos) through khuruj, particularly Haji Bakrie, who is also a Tablighi Jamaat figure. This approach is highly effective and has a significant impact on the religious reformation in the Bayan customary region. Another study indicates that TJ members have successfully negotiated their teachings with traditional practices. The society began to renounce traditional practices that were seen incompatible with Islamic teachings.